Science and Belief in the construction of the concept of Paleolithic Religion - Palacio-Pérez, Eduardo (Complutum, 2013)
The study of prehistory established itself as a scientific discipline during the second half of the nineteenth century. The main issues discussed by this new science centered on the origins of humankind, society, technology, art and religion; this intellectual process of the creation of ideas, concepts and categories was projected on the archaeological finds. When archaeological evidence was found that could be interpreted as proof of the existence of religious beliefs in Paleolithic times, there were various reactions and interpretations among prehistorians. The clash between evolutionism and the Judeo-Christian religious tradition was a key element in the development of these different discourses; these two viewpoints implied opposite ways of thinking about human nature. This paper discusses this diversity of narratives, specifically in the context of France, through the contributions of four authors, each with different ideologies and sociopolitical circumstances: Gabriel de Mortillet, Émile Cartailhac, Salomon Reinach and Henri Breuil.